Performing to type? How state institutions matter in East Central Europe - Zubek, R; Goetz, K (Cambridge University Press, 2010)
While there is much research on the developmental trajectories of post-Communist state institutions and the external and domestic influences that have shaped their paths, much less is known about institutional performance, that is, the manner in which institutions operate and the extent to which they produce predictable patterns of effects. Academic analysis has been reluctant to shift attention from institutionalisation to effects, not least because of the fluidity of many formal institutions. The present article documents that over the last decade state institutions in East Central Europe have increasingly stabilized, especially at the macro-institutional level. The analysis highlights insights from institutional theory - notably how degrees, time, preferences and resources matter - to encourage further research in the field.